Taqman qPCR Quantification and Fusarium Community Analysis to Evaluate Toxigenic Fungi in Cereals - Elina Sohlberg; Vertti Virkajärvi; Päivi Parikka; Sari Rämö; Arja Laitila; Tuija Sarlin (Toxins, 2022)
Fusarium head blight (FHB) is an economically important plant disease. Some Fusarium species produce mycotoxins that cause food safety concerns for both humans and animals. One especially important mycotoxin-producing fungus causing FHB is Fusarium graminearum. However, Fusarium species form a disease complex where different Fusarium species co-occur in the infected cereals. Effective management strategies for FHB are needed. Development of the management tools requires information about the diversity and abundance of the whole Fusarium community. Molecular quantification assays for detecting individual Fusarium species and subgroups exist, but a method for the detection and quantification of the whole Fusarium group is still lacking. In this study, a new TaqMan-based qPCR method (FusE) targeting the Fusarium-specific elongation factor region (EF1α) was developed for the detection and quantification of Fusarium spp. The FusE method was proven as a sensitive method with a detection limit of 1 pg of Fusarium DNA. Fusarium abundance results from oat samples correlated significantly with deoxynivalenol (DON) toxin content. In addition, the whole Fusarium community in Finnish oat samples was characterized with a new metabarcoding method. A shift from F. culmorum to F. graminearum in FHB-infected oats has been detected in Europe, and the results of this study confirm that. These new molecular methods can be applied in the assessment of the Fusarium community and mycotoxin risk in cereals. Knowledge gained from the Fusarium community analyses can be applied in developing and selecting effective management strategies for FHB.